PENGGUNAAN VAKSIN PRODUK EKSTRASELULER DAN INTRASELULER Aeromonas hydrophila TERHADAP RESPONS IMUN LELE DUMBO (Clarias sp.) - Mulia, Dini Siswani; Purbomartono, Cahyono (Sain Akuatik, 2009)
The aims of this research were to determine effect vaccination with extra cellular product and intracellular product of A. hydrophilic by 1-2 times booster with 2nd week time interval on African catfish immune response. The research was constructed as CRD with five treatments and three replicates, i.e. (1) E1: vaccination with extra cellular product of A. hydrophilic with one time booster; (2) E2: vaccination with extra cellular product of A. hydrophila with two times booster; (3) I1: vaccination with intracellular product of A. hydrophila with one time booster; (I2) vaccination with intracellular product of A. hydrophilic with two times booster, and (5) K: control. African catfish of 13-15 cm length and 18-21.5 g of weight were used, with the number of 15 fish for each treatment. Intramuscular injection method was conducted for vaccination and booster of 0.1 ml vaccine into the body, with the dosage of 5 Âµg/fish. Booster time interval was two weeks. Data were taken for fifteen weeks. The parameters to observe were titer antibody and water quality. Furthermore, they were analyzed by Analysis of Variance and Duncanâs Multiple Range Test (DMRT). The result showed that vaccination with extra cellular product and intracellular product of A. hydrophila by 1-2 times booster with 2nd week time interval could increase the adaptive immune response through the increase titer of antibody (P<0.05) on African catfish. Vaccination with intracellular product of A. hydrophila by two times booster (I2) was the most effective method of vaccination.